Efficacy of chemo-mechanical caries removal: a 24-month randomized trial - Kitsahawong, Kemporn; Seminario, Ana Lucia; Pungchanchaikul, Patimaporn; Rattanacharoenthum, Anoma; Sutthiprapaporn, Pipop; Pitiphat, Waranuch (Frontiers in Oral Health, 2024)
IntroductionChemo-mechanical caries removal (CMCR) offers an alternative to conventional drilling for carious dentin removal, but limited evidence exists on its long-term effects on treating caries in primary teeth. The primary aims of this study were to compare CMCR to drilling in terms of restoration status and the presence of secondary caries after 24 months.MethodsA randomized, parallel-group, single-blinded, controlled trial was conducted in Thailand. Participants were children aged 7–8 years with occlusal caries in second primary molars, randomly assigned to CMCR with Papacarie® (n = 242) or drilling (n = 246). All cavities were restored using glass ionomer cement. Completeness of caries removal was evaluated clinically by two blinded dentists, and patients' discomfort was measured using a facial visual analogue scale. Restoration status and development of secondary caries were assessed every six months clinically and every 12 months radiographically over a 2-year period.ResultsBoth groups achieved complete caries removal, but the CMCR took significantly longer than the drilling method (9 vs. 2.3 min, p < 0.001). Children in the CMCR group reported significantly lower discomfort during treatment (p < 0.001). At 24 months, ten (4.6%) restorations in the CMCR group failed, compared to three (1.2%) in the drilling group. Clinically, four restorations (CMCR = 2, control = 2) exhibited secondary caries at the margin, while nine restorations (CMCR = 8, control = 1) showed radiographic evidence of secondary caries beneath the restoration. However, neither clinical nor radiographic evaluations revealed statistically significant differences in treatment outcomes at the two-year mark.ConclusionCMCR demonstrated comparable efficacy to conventional drilling for complete caries removal and restoration success at 24 months in primary teeth. Despite a longer chair time, it resulted in less discomfort during treatment.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT01641861, identifier: NCT01641861.